1983
DOI: 10.1161/01.hyp.5.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Childhood familial and racial differences in physiologic and biochemical factors related to hypertension.

Abstract: SUMMARY Early differences in hemodynamic variables and vasoactive substances between progeny of hypertensive and normotensive parents were sought in normotensive children aged 10-17 years. Forty-two black and 34 white children of hypertensive parents (cases) and an age-balanced group of 20 black and 45 white children of normotensive parents (controls) underwent exercise stress testing. Blood pressure, heart rate, urinary electrolytes, kallikrein, and prostaglandin E-like material, plasma renin activity, and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

1987
1987
2000
2000

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 50 publications
0
24
1
Order By: Relevance
“…Moreover, PRA distributions are not normal, although there is no evidence for a bimodal distribution in blacks. A lower plasma PRA has also been observed in some 10,17 but not in every study 18,19 of black children compared with white children, however, it is apparent that the difference between black and white children becomes more pronounced with increasing age even over an age range of 8-14 years. 17 Interestingly, slightly lower PRA has also been reported in black neonates.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 86%
“…Moreover, PRA distributions are not normal, although there is no evidence for a bimodal distribution in blacks. A lower plasma PRA has also been observed in some 10,17 but not in every study 18,19 of black children compared with white children, however, it is apparent that the difference between black and white children becomes more pronounced with increasing age even over an age range of 8-14 years. 17 Interestingly, slightly lower PRA has also been reported in black neonates.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 86%
“…30 Suppression of the renin-angiotensin system has been demonstrated. [31][32][33] We have found a higher plasma renin activity (PRA) in rural compared to urban Zulus. This suggests that the cause of a low PRA in black subjects may not be genetic.…”
Section: Determinant Factors Of Hypertension In Black Subjectsmentioning
confidence: 99%
“…12 Renin is lower in black people and does not increase in response to sodium and volume depletion. [13][14][15][16] The distribution curve of plasma renin in black Americans is not 'normal' but rather logarithmic, in contrast to the curve found in whites. 13 We have found that rural Zulus have higher plasma renin activity (PRA) compared to urban Zulus.…”
Section: National Health and Nutritional Survey (Nhanes)mentioning
confidence: 99%